GCA links TRAF6-ULK1-dependent autophagy activation in resistant chronic myeloid leukemia. Issue 12 (2nd December 2019) - Han, Seung Hun; Korm, Sovannarith; Han, Ye Gi; Choi, Soo-Young; Kim, Soo-Hyun; Chung, Hee Jin; Park, Kibeom; Kim, Jae-Young; Myung, Kyungjae; Lee, Joo-Yong; Kim, Hongtae; Kim, Dong-Wook
ABSTRACT: Imatinib is the first molecularly targeted compound for chronic myeloid leukemia (CML) capable to inhibit BCR-ABL kinase activity. However, recent clinical evidence indicates that a substantial proportion of CML patients exhibit BCR-ABL-dependent or independent resistance to imatinib. Despite the importance of imatinib resistance in CML, the underlying molecular mechanisms of this resistance are largely unknown. Here, we identified GCA (grancalcin) as a critical regulator of imatinib resistance in chronic phase CML via activation of autophagy. Mechanistically, we demonstrated that GCA activates TRAF6 ubiquitin ligase activity to induce Lys63 ubiquitination of ULK1, a crucial regulator of autophagy, resulting in its stabilization and activation. We also highlighted the role of GCA-TRAF6-ULK1 autophagy regulatory axis in imatinib resistance. Our findings represent the basis for novel therapeutic strategies against CML. Abbreviation: ACTB/β-actin: actin beta; ADM: adrenomedullin; AMBRA1: autophagy and beclin 1 regulator 1; AMPK: AMP-activated protein kinase; ANXA5: annexin A5; CP: cytogenetic response; CML: chronic myeloid leukemia; CUL3: cullin 3; GAPDH: glyceraldehyde-3-phosphate dehydrogenase; GCA: grancalcin; Dx: at diagnosis; E-64-d: (2S, 3S)-trans-Epoxysuccinyl-L-leucylamido-3-methylbutane ethyl ester; IMres: Imatinib resistance; KLHL20: Kelch-like protein 20; LRMP: lymphoid-restricted membrane protein; MAP1LC3/LC3: microtubule associated protein 1 light chain 3; MMR: major molecular response; NH4 Cl: ammonium chloride; PBMCs: peripheral blood mononuclear cells; PTPRC: protein tyrosine phosphatase, receptor type, C; SQSTM1/p62: sequestosome 1; SYK: spleen associated tyrosine kinase; TAP1: transporter 1, ATP binding cassette subfamily B member; TKIs: ABL-specific tyrosine kinase inhibitors; TLR9: toll- like receptor 9; TRAF6: TNF receptor associated factor 6; ULK1: unc-51 like autophagy activating kinase 1